Legal Protection for Non-Procedural Indonesian Migrant Workers as Victims of Human Trafficking Crimes - Utomo, Lutfi Erlangga Risky; Arifin, Ridwan (Universitas Negeri Semarang, 2025)
Irregular Indonesian migrant workers are a vulnerable group frequently subjected to human trafficking due to their undocumented and unlawful departure processes. Their absence from the official labor placement system leaves them outside the scope of state protection and exposes them to various forms of exploitation. This study aims to analyze the legal framework and implementation of protection for irregular Indonesian migrant workers as victims of human trafficking, as well as to identify the key obstacles hindering the effectiveness of such protection. Employing a normative juridical method, this research uses statutory and case-based approaches. The findings indicate that while Indonesia has established a relatively comprehensive legal framework through Law No. 18 of 2017 and Law No. 21 of 2007, its implementation remains suboptimal, particularly in reaching undocumented victims. Substantive, institutional, and socio-cultural barriers continue to undermine equitable protection efforts. Therefore, a holistic approach grounded in non-discrimination and victimology principles, along with strengthened cross-sectoral coordination, is essential to ensure the realization of victims’ rights in a meaningful and sustainable manner.